(untitled) (Anclajes, 2022)
On the basis of cover art and advertising development at the beginning of the twentieth century, at a key time of periodics publishing History in Argentina (in terms of the offer of growth and diversification), this work analyzes the uses of writer’s portrait in Los Pensadores between 1922 and 1924, the booklet with which Antonio Zamora (1896-1976) launched Claridad publishing house. On one hand, the analysis of this periodics covers, as well as other composition decisions, allows to compare the strategies of both periodical press and cheap book publishers in the 1920 publishing field. On the other hand, different material features such as the choice of images or graphical and editorial decisions lead to give an account of their taking part in the process of author’s figure fixing on the book artefact. By this way, they also give empiricity to author’s function, under media regime and in the context of mass culture.